MITIGASI RISIKO RANTAI PASOK TEH MAHKOTA DEWA (Studi Kasus di CV Salama Nusantara, Kabupaten Kulon Progo, Daerah Istimewa Yogyakarta) - Wahyuni, Dian Assifa Dwi; Kusno, Kuswarini (Universitas Galuh, 2023)
CV Salama Nusantara is a company that produces mahkota dewa tea using main ingredients such as dried mahkota dewa, green tea, and parasite of tea. The quantity of mahkota dewa tea raw material purchased in 2022 has fluctuated due to supply chain problems from suppliers and unstable market demand conditions due to the Covid-19 pandemic. The disruption in the supply chain has caused risks to the supply chain activities, resulting in a slight delay in the production of mahkota dewa tea this year. This study aims to identify the risks that occur in the supply chain activities and obtain mitigation to handle priority risks in the supply chain activities of mahkota dewa tea in CV Salama Nusantara.. The design applied in this research is quantitative with case study research techniques. Based on the research results, there are 31 risk events and 15 risk agents in the mahkota dewa tea supply chain at CV Salama Nusantara. There are six priority risk agents, namely scarcity or disruption of raw material supply, dependence on only one supplier, human error, distant supplier location, main or supporting raw materials unavailable, and disruptions during transportation. Furthermore, risk mitigation that needs to be done by CV Salama Nusantara includes creating contracts with suppliers, managing raw material inventory, planning safety stock of raw materials, searching for new suppliers, planning transportation modes for raw material delivery, distributing job descriptions to employees, evaluating supplier performance, improve SOP, arranging production areas, and making agreements with shipping service providers regarding product delivery quality assurance.